1968
DOI: 10.1111/j.1365-2621.1968.tb09080.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Pigments of Rhubarb, Canada Red

Abstract: SUMMARY The anthocyanin pigments of rhubarb (Rheum rhaponticum‘Canada Red’) were extracted with 0.02% methanolic HCI and partially purified by use of cation‐exchange resin. The pigments were separated into two bands with paper and cellulose thin‐layer chromatography. The purified pigments were characterized by their R, values, partial acid hydrolysis, identification of the aglycones and sugars after complete hydrolysis, and their spectral properties. The main pigment (87% of the total anthocyanins) was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the early eluting components, we found substantial amounts of two anthocyanins (cyanidin 3-O-rutinoside and cyanidin 3-Oglucoside; Wrolstad & Heatherbell, 1968) and evidence for the presence of a range of proanthocyanidins and quercetin derivatives.…”
Section: Resultsmentioning
confidence: 96%
“…In the early eluting components, we found substantial amounts of two anthocyanins (cyanidin 3-O-rutinoside and cyanidin 3-Oglucoside; Wrolstad & Heatherbell, 1968) and evidence for the presence of a range of proanthocyanidins and quercetin derivatives.…”
Section: Resultsmentioning
confidence: 96%
“…), but their identities were unknown, so only proportions of the two major anthocyanins were reported. Wrolstad & Heatherbell () reported that cyanidin 3‐glucoside and cyanidin 3‐rutinoside comprised 87% and 13% of the total anthocyanins, respectively, in the rhubarb variety, Canada Red. Fuleki () examined four rhubarb varieties and found they contained cyanidin 3‐glucoside and cyanidin 3‐rutinoside in the following percentages: German Wine (33% and 66%), Sunrise (48% and 51%), Sutton's Seedless (48% and 50%) and Valentine (58% and 41%).…”
Section: Resultsmentioning
confidence: 99%
“…Rhubarb has been touted as top source of antioxidant phenols (Dimitrios, 2006) based on its anthocyanin content of up to 2000 mg kg À1 (Clifford, 2000). Rhubarb contains two major anthocyanins, cyanidin 3-glucoside and cyanidin 3-rutinoside (Gallop, 1965;Wrolstad & Heatherbell, 1968;Fuleki, 1969). Cyanidin 3-glucoside has been shown to inhibit tumour promoter-induced carcinogenesis and tumour metastasis in vivo (Ding et al, 2006).…”
mentioning
confidence: 99%
“…After elution of the anthocyanin fraction on Toyopearl HW40(S) with methanol and after equilibration or regeneration of the bed with acetone and water, the column is ready for rechromatography. Other fruits reported to contain cyanidin-3-glucoside and cyanidin-3-rutinoside are rhubarb 13 and capulin. 14 Bird cherry fruit is rich in anthocyanins, similarly to the well-known and rich anthocyanin sources such as chokeberry, bilberry, honeysuckle and elderberry, which are particularly useful in the production of juices, fruit drinks and wines.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shifts were recorded as parts per million (ppm) downfield from the solvent as reference. 13 C signals were assigned from a DEPT experiment and from comparisons with data reported by Terahara et al 3…”
Section: Thin Layer Chromatography Of Sugarsmentioning
confidence: 99%